MONITORING DAN ANALISIS IP CAMERA PADA JARINGAN INTERNET - ., Ajie Pambudhi (Faculty of Engineering, Universitas Tanjungpura, 2017)
IP Camera is one type of surveillance camera system that allows users to monitor a room or a specific place. The recording of the camera is stored on an NVR (Network Video Recorder) device and to display the recording of the camera using a PC monitor. For monitoring, usually using a local network, this is certainly not effective if the room is abandoned by the owner. In this final project configure IP Camera to be accessed through internet network and evaluate QoS internet network. From the research results can be concluded that IP camera monitoring can be done through internet network. The average internet access speed measurement at the Faculty of Engineering Tanjungpura University for download and upload each valued at 10.81 Mbps and 6.39 Mbps. The delay result is 186.50 ms. Compared to the standardized network performance based on TIPHON, it is included in the